2021
DOI: 10.31234/osf.io/xr3st
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics of smartphone-based dietary assessment tools: A systematic review

Abstract: Smartphones have become popular in assessing eating behaviour in real-life and real-time. This systematic review provides a comprehensive overview of smartphone-based dietary assessment tools, focusing on how dietary data is assessed and its completeness ensured. Seven databases from behavioural, social and computer science were searched in March 2020. All observational, experimental or intervention studies and study protocols using a smartphone-based assessment tool for dietary intake were included if they re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 112 publications
0
10
0
Order By: Relevance
“…Since truly objective digital assessment of consumption behaviours in daily life including smoking, alcohol consumption, and food intake is still in its early stages (21,48), it was decided prior to screening titles and abstracts that Ecological Momentary Assessment (EMA) (18) of consumption behaviours would be considered as long as participants were asked to record the occasion immediately before, during or after consumption, preferably using objective markers such as a photo (21) which minimises recall bias (18).…”
Section: Deviations From the Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Since truly objective digital assessment of consumption behaviours in daily life including smoking, alcohol consumption, and food intake is still in its early stages (21,48), it was decided prior to screening titles and abstracts that Ecological Momentary Assessment (EMA) (18) of consumption behaviours would be considered as long as participants were asked to record the occasion immediately before, during or after consumption, preferably using objective markers such as a photo (21) which minimises recall bias (18).…”
Section: Deviations From the Protocolmentioning
confidence: 99%
“…Consumption behaviours such as medication adherence, alcohol consumption, smoking, and eating behaviour were rarely studied, which may be the case because they are more difficult to assess digitally than physical activity, for which passive tracking is well established. Most notably, although digital assessment of dietary intake including objective indicators such as photos is common in behavioural research (21), measurement reactivity has not yet been studied in this domain: Apart from one study that investigated the consumption of both alcoholic and non-alcoholic drinks during nights out, no studies on dietary intake were identified. Future research needs to address this gap to provide important information on the validity of digital assessment of dietary intake as well as other consumption behaviours.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilisation of more objective data collection, in parallel with self-reported behavioural outcomes, such as food photos, could also help improving the evaluation of these interventions. 75…”
Section: Limitations Of Previous Individual Behaviour Change Interven...mentioning
confidence: 99%
“…The ubiquity of smartphones and their integration into every facet of life has made it possible to monitor one's health status such as vital signs, exercise and sleep statistics, etc. What and how much a person eats and drinks in a day is another key contributor to one's overall health, yet very difficult to assess [1]. Many existing mobile applications rely on manual user input to capture information about the foods they consumed [2].…”
Section: Introductionmentioning
confidence: 99%